Levels of vascular endothelial growth factor in patients with rheumatoid arthritis - Ardicoglu, Ozge; Boz, Kenan; Kamanli, Ayhan; Kavuncu, Vural; Canatan, Halit; Onal, Suleyman; Ozgocmen, Salih (My University, 2004)
Background: Rheumatoid Arthritis (RA) is a chronic, progressive connective tissue disease characterized by deformities affecting joints. In recent years, the effect of angiogenesis in synovial tissue hypertrophy along with inflammation has been emphasized. Factors involved in angiogenesis also contribute to the pathogenesis and progression of RA. Objective: In the present study, serum vascular endothelial growth factor (VEGF) levels of patients with RA were determined and the relationship between VEGF and other cytokines which have roles in inflammation were evaluated. Material and method: The study was performed in 38 RA patients, and age and sex matched 40 healthy volunteers. IL-2, IL-6, IL-8, and TNF-? serum levels of the groups were assayed using commercially avalaible ELISA kits. VEGF levels were determined using a quantitative sandwich enzyme immunoassay technique according to manifacturer's instructions. Results and conclusion: VEGF serum levels were statistically significantly higher (p < 0.01) in patients with RA (395 ± 342 pg/ml) than in controls (233 ± 142 pg/ml). IL-2, IL-6, IL-8, and TNF-? cytokine levels were significantly higher in patients with RA than in controls. A positive correlation was found between IL-8 and VEGF levels. There was no correlation between VEGF levels and ESR, CRP, RF levels. We observed that VEGF values were not affected by the use of DMARDs. In conclusion, we have demonstrated that IL-8 is an important chemotactic factor, and that VEGF is a necessary cytokine for pathologic angiogenesis.
Keywords: Angiogenesis; IL-8; Rheumatoid arthritis; Vascular endothelial growth factor